Fetal intervention for severe lower urinary tract obstruction: a multicenter case–control study comparing fetal cystoscopy with vesicoamniotic shunting. (2nd March 2015) - Ruano, R.; Sananes, N.; Sangi‐Haghpeykar, H.; Hernandez‐Ruano, S.; Moog, R.; Becmeur, F.; Zaloszyc, A.; Giron, A. M.; Morin, B.; Favre, R.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 375–376